Late Jurassic and Early Cretaceous Radiolarian Age Determinations from Timor-Leste - Munasri, Munasri; Charlton, Timothy Richard; Guterres, Maria; Gandara, Dino (Berita Sedimentologi, 2024)
Two new sets of palaeontological age determinations based on radiolaria are reported from Timor-Leste. The first is from the Suai Loro-1 petroleum exploration well, located near Suai town in SW Timor-Leste, drilled by Timor Oil in 1971. Newly rediscovered ditch cutting samples from the previously undated basal section of this well have yielded radiolarians of Late Jurassic (middle Oxfordian to middle Kimmeridgian) age. On lithology, this stratigraphic interval of reddish shales and interbedded limestones is assigned to the Tchinver Formation.A second set of radiolarian determinations is from samples collected in the Caraulun river south of Samé town in south-central Timor-Leste. These are dated to the Early Cretaceous (late Valanginian-Hauterivian). The outcrop succession of radiolarian cherts, sandstones and red shales are assigned to the Wai Bua Formation as defined in East Timor (Timor-Leste), which is equivalent to the Nakfunu Formation in Indonesian West Timor.